Investigation of silicon nanoparticles produced by centrifuge chemical vapor deposition for applications in therapy and diagnostics - Lumen Dave; Wang Shiqi; Mäkilä Ermei; Imlimthan Surachet; Sarparanta Mirkka; Correia Alexandra; Westerveld Haug Christina; Hirvonen Jouni; Santos Hélder A; Airaksinen Anu J; Filtvedt Werener; Salonen Jarno (Elsevier, 2022)
Porous silicon (PSi) is a biocompatible and biodegradable material, which can be utilized in biomedical applications. It has several favorable properties, which makes it an excellent material for building engineered nanosystems for drug delivery and diagnostic purposes. One significant hurdle for commercial applications of PSi is the lack of industrial scale production of nanosized PSi particles. Here, we report a novel two-step production method for PSi nanoparticles. The method is based on centrifuge chemical vapor deposition (cCVD) of elemental silicon in an industrial scale reactor followed by electrochemical post-processing to porous particles. Physical properties, biocompatibility and in vivo biodistribution of the cCVD produced nanoparticles were investigated and compared to PSi nanoparticles conventionally produced from silicon wafers by pulse electrochemical etching. Our results demonstrate that the cCVD production provides PSi nanoparticles with comparable physical and biological quality to the conventional method. This method may circumvent several limitations of the conventional method such as the requirements for high purity monocrystalline silicon substrates as starting material and the material losses during the top-down milling process of the pulse-etched films to porous nanoparticles. However, the electroless etching required for the porosification of cCVD-produced nanoparticles limited control over the pore size, but is amenable for scaling of the production to industrial requirements.